Effect of Convalescent Plasma in Critically Ill Patients With COVID-19: An Observational Study - Kurtz, Pedro; Righy, Cassia; Gadelha, Monica; Bozza, Fernando A.; Bozza, Patricia T.; Gonçalves, Bruno; Bastos, Leonardo S. L.; Vale, Andre M.; Higa, Luiza M.; Castilho, Leda; Monteiro, Fabio L.; Charris, Nestor; et al. (Frontiers in Medicine, 2021)
Background: Convalescent plasma is a potential therapeutic option for critically ill patients with coronavirus disease 19 (COVID-19), yet its efficacy remains to be determined. The aim was to investigate the effects of convalescent plasma (CP) in critically ill patients with COVID-19. Methods: This was a single-center prospective observational study conducted in Rio de Janeiro, Brazil, from March 17th to May 30th, with final follow-up on June 30th. We included 113 laboratory-confirmed COVID-19 patients with respiratory failure. Primary outcomes were time to clinical improvement and survival within 28 days. Secondary outcomes included behavior of biomarkers and viral loads. Kaplan–Meier analyses and Cox proportional-hazards regression using propensity score with inverse-probability weighing were performed. Results: 41 patients received CP and 72 received standard of care (SOC). Median age was 61 years (IQR 48–68), disease duration was 10 days (IQR 6–13), and 86% were mechanically ventilated. At least 29 out of 41CP-recipients had baseline IgG titers ≥ 1:1,080. Clinical improvement within 28 days occurred in 19 (46%) CP-treated patients, as compared to 23 (32%) in the SOC group [adjusted hazard ratio (aHR) 0.91 (0.49–1.69)]. There was no significant change in 28-day mortality (CP 49% vs. SOC 56%; aHR 0.90 [0.52–1.57]). Biomarker assessment revealed reduced inflammatory activity and increased lymphocyte count after CP. Conclusions: In this study, CP was not associated with clinical improvement or increase in 28-day survival. However, our study may have been underpowered and included patients with high IgG titers and life-threatening disease. Clinical Trial Registration: The study protocol was retrospectively registered at the Brazilian Registry of Clinical Trials (ReBEC) with the identification RBR-4vm3yy (http://www.ensaiosclinicos.gov.br).